Iron–Cobalt Phosphomolybdate with High Electrocatalytic Activity for Oxygen Evolution Reaction. Issue 20 (21st September 2017) - Zhai, Haoying; Gao, Taotao; Qi, Ting; Zhang, Yajie; Zeng, Guangfeng; Xiao, Dan
Abstract: Iron–cobalt phosphomolybdate (FeCoPM12 ) nanoparticles, which are highly efficient catalytic materials for the oxygen evolution reaction (OER), were fabricated through a coprecipitation route. Compared with iron–cobalt hydroxide and state‐of‐the‐art RuO2 electrocatalysts, the as‐prepared FeCoPM12 sample exhibited robust OER catalytic activity with a low overpotential of 258 mV at a current density of 10 mA cm −2 and a small Tafel slope of 33 mV dec −1 . Moreover, the as‐synthesized sample presented preferable stability and after 10 h at 1.52 V the current density degraded by merely 8.3 %. This is ascribed to the high electrochemical stability and small porous structure of FeCoPM12, which provide effective electron transmission and improve the catalytic performance for OER in alkaline media. Abstract : Coworking metals : FeCoPM12 nanoparticles, with high electrochemical stability and catalytic performance for the oxygen evolution reaction (OER), were fabricated through a coprecipitation route. Compared with iron–cobalt hydroxide and state‐of‐the‐art RuO2 electrocatalysts, the FeCoPM12 catalyst possesses a low overpotential of 258 mV at a current density of 10 mA cm −2 and a small Tafel slope of 33 mV dec −1 (see figure).